سیرتِ نبوی ﷺ کی روشنی میں غربت کے خاتمے اور دولت کی منصفانہ تقسیم کا تجزیاتی مطالعہ: An Analytical Study of Poverty Alleviation and Equitable Distribution of Wealth in the Light of the Sirah of the Holy Prophetﷺ - Amna Baigum; Dr. Mian Muhammad Ali Awais; Shamim Akhtar (Al-Amīr Research Journal for Islamic Studies, 2024)
People in any state who do not have the basic necessities of food, clean water, clothing, housing and financial resources for basic health are considered as poor. In order to solve economic problems, where Islam has given orders taking into account its various points, it has also paid attention to the elimination of poverty and unemployment and their solutions through various causes and means related to these problems in the society, methods are also described. Poverty and unemployment are problems that not only hinder the development of the society but also affect the morals and beliefs of the people affected by these problems. Just as the world is suffering from problems like poverty and unemployment in the present situation, it has also been suffering from such problems before. The Prophet (PBUH) took practical steps based on Islamic teachings and orders to get out of this problem. Zakat, Sadaqah al-Fitr, Infaq fi Sabil Allah have been ordered for the eradication of poverty and distribution of wealth. This paper aims to highlight the modes and techniques through which the poverty rate can be reduced in light of the teachings of Islam at different level i.e. individual, society and government. This article has also highlighted the methods to reduce poverty and distribution of wealth. This paper recommended that Muslim Ummah should follow the teachings of the Prophet (PBUH) to economic growth and distributions of wealth. Key words: Poverty, Islamic modes of wealth distribution, Methods to reduce poverty.